CENSUS 2022 - POPULATION OF SERBIA ACCORDING TO NATIONALITY - Raduski, Nada (Serbian political thought, 2024)
Ethno-demographic and ethno-statistical studies of the population of Serbia according to nationality are based on the census as the most important official source of data, which is held every ten years and provides information on demographic trends, the number and characteristics of all ethnic communities in Serbia, but also provides a database for the adoption of necessary measures population, social, economic, minority and other state policies important for the stable, even and prosperous development of the country. The paper highlights the impact of various factors on national declaration, as well as the buoyancy of this feature, whose subjectivity has influenced large fluctuations in the number of individual ethnic communities, as well as the accuracy and possibility of comparing census results. Changed census methodology, new methodological solutions, criteria, classifications, definitions, often as a result of national ideology, political decisions and social circumstances, had a great immediate impact on the changes in the population dynamics of all, and especially some nationalities. The paper analyzes the national composition of the population of Serbia (without Kosovo and Metohija) according to the data of the last census from 2011, as well as the significant demographic changes that occurred in the period between the two censuses (2011-2022), while looking at the similarities and differences between the regions. of Serbia (Belgrade region, Vojvodina region, Šumadija and Western Serbia region and Southern and Eastern Serbia region). The focus of the research is on the most important factors that influenced the change in the ethnic structure, such as differences in the rates of natural increase and migration balance according to nationality, but also ethnic alternation under the influence of numerous non-demographic, namely political, social, economic, religious, psychological and other factors. The different population dynamics of ethnic communities, i.e. the increase in the number and share of some, while at the same time the decrease in the number of others, determined the direction and intensity of changes and affected the national composition of the population, as well as the process of ethnic homogenization or dispersiveness of individual nationalities, which created and changed everything the ethnic image of Serbia.
Keywords: census, methodology, nationality, demographic dynamics, regions, Serbia